1997
DOI: 10.1021/ja970262+
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of Pd4(μ-PtBu2)2(μ-CS2)(PPh3)2I2, a Neutral Palladium(I) Derivative with a Hexacoordinate Carbon and a CS2 Molecule Bridging Four Palladium Centers

Abstract: The dinuclear CS2 complex [Pd2(μ-PtBu2)(μ,η2:η2-CS2)(PPh3)2]BF4, (2)BF4, reacts with Me4NI to yield the neutral tetranuclear Pd(I) derivative Pd4(μ-PtBu2)2(μ4-CS2)(PPh3)2I2 (4), which has been characterized by single-crystal X-ray diffraction. Its unusual molecular structure with a formally hexacoordinate carbon atom, as well as that of (2)+ with a planar tetracoordinate carbon can be explained on the basis of fragment MO considerations and EHMO model calculations. The reaction proceeds stepwise, with the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…General theoretical ideas have been reported that substantiate the above models. In particular, a qualitative MO analysis of the CS 2 adduct 1 4 has been presented . Also there are ab initio studies for the allyl derivative with one halide in place of the phosphido bridge .…”
Section: Resultsmentioning
confidence: 99%
“…General theoretical ideas have been reported that substantiate the above models. In particular, a qualitative MO analysis of the CS 2 adduct 1 4 has been presented . Also there are ab initio studies for the allyl derivative with one halide in place of the phosphido bridge .…”
Section: Resultsmentioning
confidence: 99%
“…16,17 The reported organometallic chemistry of CS 2 with transition metals includes examples such as the p-bound and bridged CS 2 ligand on a metal framework, insertion of CS 2 into an M-X bond (X = H, N, C, O) and coupling reactions. 14,16,18 Moreover, CS 2 has been observed to cleave, leading to the formation of thiocarbene, trithiocarbonate, or thiocarbonyl ligands. 19,20 Because of ever-growing interest in the activation of CS 2 from catalytic, synthetic and biological points of view, 13,[16][17][18][19][20][21][22] we have studied the reactions of [(m-RS)Fe 2 (CO) 6 (m-SCS À )] with Fe 3 (CO) 12 and Ph 2 PCl.…”
mentioning
confidence: 99%
“…14,16,18 Moreover, CS 2 has been observed to cleave, leading to the formation of thiocarbene, trithiocarbonate, or thiocarbonyl ligands. 19,20 Because of ever-growing interest in the activation of CS 2 from catalytic, synthetic and biological points of view, 13,[16][17][18][19][20][21][22] we have studied the reactions of [(m-RS)Fe 2 (CO) 6 (m-SCS À )] with Fe 3 (CO) 12 and Ph 2 PCl. 23 In this communication we describe the unexpected results.…”
mentioning
confidence: 99%
“…(1) can be generalised to other diphosphines and other acetylacetones [eqn. (2)]. Hence the ligands 3-5a,b have been made in high yield as mixtures of diastereoisomers using the appropriate H 2 P(CH 2 ) n PH 2 and 1,3-diketone.…”
mentioning
confidence: 99%